2002
DOI: 10.1183/09031936.02.00238402
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic deprivation and asthma prevalence and severity in young adolescents

Abstract: This study used the international study of asthma and allergies in childhood (ISAAC) to investigate the association between asthma and socioeconomic deprivation among young adolescents in Cape Town, South Africa.The completed ISAAC written and video questionnaires of 4,706 13-14-yr-old school pupils were used. The prevalence of asthma symptoms was analysed by a local index of socioeconomic deprivation, based on residential location and defined on a 10-category scale from least to most deprived. Linear trends w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
1
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 25 publications
8
44
1
1
Order By: Relevance
“…The fact that the prevalence of wheeze, allergic rhinitis and atopic eczema symptoms was lower in high-SES school children was opposite to the finding from a previous study conducted in children attending 30 schools in socio-economically diverse areas of Cape Town, South Africa, which reported that the prevalence of asthma, recent wheeze and allergic rhinitis increased from lowest to highest SES [28,29]. One of the possibilities to consider is that certain viral infections, which might be associated with allergy-like symptoms and difficult to differentiate from real allergy by parents, were more prevalent in the low-SES children of the current study [30,31].…”
Section: Discussioncontrasting
confidence: 55%
“…The fact that the prevalence of wheeze, allergic rhinitis and atopic eczema symptoms was lower in high-SES school children was opposite to the finding from a previous study conducted in children attending 30 schools in socio-economically diverse areas of Cape Town, South Africa, which reported that the prevalence of asthma, recent wheeze and allergic rhinitis increased from lowest to highest SES [28,29]. One of the possibilities to consider is that certain viral infections, which might be associated with allergy-like symptoms and difficult to differentiate from real allergy by parents, were more prevalent in the low-SES children of the current study [30,31].…”
Section: Discussioncontrasting
confidence: 55%
“…Fuel type used for cooking may be related to socio-economic status (SES). However, unlike atopy that is more common in higher SES groups [29], the influence of SES on asthma prevalence or incidence is conflicting [30][31][32]. Differences in study methodologies may be one of the reasons for these conflicting findings.…”
Section: Discussionmentioning
confidence: 67%
“…First of all a distinction must be made between risk of asthma ever (lifetime risk) and current symptoms [2]. Gross national product per capita is generally associated with both an increasing prevalence of wheezing ever and wheezing in the last 12 months [7].…”
Section: Poverty and Risk Of Asthmamentioning
confidence: 99%
“…This has not generally been the pattern for asthma, where the lifetime prevalence of symptoms is usually higher in more affluent societies [2,3], and a rising prevalence of asthma is a price paid for increasing national prosperity. This trend is probably inevitable since to date, no public health strategy for large-scale primary prevention of asthma has yet proved feasible or effective.…”
mentioning
confidence: 99%